Das Papyrusportal - Reinhold Scholl; Jens Kupferschmidt; Marius Gerhardt; Stefan Freitag (Digital Classics Online)
The ‚Papyrus Portal‘ is a project that aims to provide the user with an efficient and effective search of all digitized and electronically catalogued papyrus collections in Germany, and a unified presentation of the search results with the most important information on the particular papyrus. This includes links to the local home databases which have more details on each piece. The ‚Papyrus Portal‘ unites the different information technologies of the original databases and presents the search results in a standard format. A conventional format for the recording of the metadata has been established.